Nefazodone shortage in the United States: analysis of drug switching and utilization - Tabah, Ashley; Fox, Julia; English, Clayton (Frontiers in Psychiatry, 2025)
IntroductionMedication shortages and manufacturer discontinuations of antidepressants place patients in vulnerable scenarios if medications become inaccessible, leaving prescribers to alter therapy without guarantee of a sustained response to the new treatment.MethodsWe conducted a descriptive retrospective analysis to explore changes in drug utilization and switching patterns following an FDA-declared nefazodone shortage in the United States. Using the Komodo Healthcare Map®, we analyzed prescribing patterns across the pre-shortage, shortage, and post-shortage periods.ResultsA total of 7891 individuals were selected for inclusion, with 2185 eligible for the switching outcomes. A majority (96.4%) switched to an alternative medication, with an average time to switch of 106.8 days (SD: 81.7). Few patients resumed nefazodone use post-shortage (7.3%).DiscussionAlthough most patients transitioned to alternative antidepressants during the shortage, the need for treatment changes and the low rate of returning to the original medication may reflect challenges to patient-centered care. There is a need for clearer prescriber guidance to better support clinical decision-making during medication shortages.